Effects of a physical activity program on the sleep quality of schoolchildren with ADHD - López Sánchez, G. F.; López Sánchez, L.; Díaz Suárez, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
This paper focuses on studying the effects of a physical activity program on sleep quality of a group of schoolchildren with Attention Deficit Hyperactivity Disorder (ADHD). This investigation involved 12 students (12 boys), aged between 7 and 12 years. The sleep quality was measured by Pittsburg’s Sleep Quality Index. The procedure was as follows: pre-test, intervention and post-test. The intervention consisted of 2 days per week of physical activity, 60 minutes per day, during 12 weeks. 16.6 % of schoolchildren have increased their sleep quality. After the physical activity program, some schoolchildren have maintained their sleep quality and others have increased it.